Hubungan Bimbingan Orang Tua Dengan Motivasi Belajar Pendidikan Agama Islam Siswa SDIT Rabbani Rajeg Kabupaten Tangerang - Zubairi Zubairi; Nurdin Nurdin; Tiara Zain Halida (LP. Ma'arif Janggan Magetan, 2023)
This study aims to investigate the relationship between parental guidance and the motivation to study Islamic Religious Education of students at SDIT Rabbani Rajeg, Tangerang Regency. The research method used is a quantitative research method using a questionnaire as a data collection instrument. The research sample consisted of students at SDIT Rabbani who were selected by simple random sampling. In this study there is a positive and meaningful relationship between parental guidance and student learning motivation (specifically in Islamic Religion subjects), the contribution of x to y is shown by a correlation coefficient of 0.951 with a coefficient of determination of 90%. This means that parents contribute 90% of the learning motivation of SDIT Rabbani students. The sample in this research, the authors determined 40 students out of a total of 153 students. Based on research from Suharsimi Arikunto, namely: